Testing the viability of using the Posner framework for detecting collusive price behavior using economic evidence : - Cameron, Pamela J. (The University of Oklahoma., 1985)
To be viable an approach must have widespread, general applicability and be capable of gaining widespread acceptance among economists. The case study application produced results which proved that the basic Posner framework can be extended and applied in all markets with the exception of a true, high concentrated, national oligopoly. In such industries the absence of collusive behavior could be established.

Acceptance will be influenced heavily by the willingness of economists to include tacit collusion (conscious parallel action) within the realm of conduct deemed to be an economic restraint of trade.

For purposes of implementing the proposed technique, an actual price-flying case filed pursuant to Section 1 of the Sherman Act was selected. Since the case involved a regulated industry, the economic and legal impact of regulation on the underlying economic, theoretical framework was analyzed.

A case study approach is used to test the efficacy of the proposition put forth by Richard Posner that by implementing his framework the presence or absence of collusion can be detected using purely economic evidence. His framework consists of a two stage analysis in which twenty-four economic variables or indicia are employed to determine whether or not the firms involved show any evidence of collusive behavior and whether or not the industry is conducive to collusion.
Keywords: Antitrust law.; Economics, Commerce-Business.; Price regulation.